2017
DOI: 10.1177/2050640616681909
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic approach for management of biliary strictures in liver transplant recipients: A systematic review and meta‐analysis

Abstract: The most common biliary complication after liver transplantation is anastomotic stricture (AS) and it can occur isolated or in combination with other complications. Liver graft from a cadaveric donor or a living donor has an influence on the incidence of biliary strictures as well as on the response to endoscopic treatment. Endoscopic treatment using balloon dilation and insertion of biliary stents by endoscopic retrograde cholangiopancreatography (ERCP) is the initial approach to these complications. Aim: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 59 publications
1
25
0
Order By: Relevance
“…The incidence of initial treatment failure was lower with balloon dilatation alone (5%) than with balloon dilatation with plastic stent (8%). However, this meta-analysis also found that the rate of stricture recurrence was higher when initial treatment was with balloon dilatation alone versus balloon dilatation and stent placement (33% versus 27%) [51].…”
Section: Variant 3: Initial Therapeutic Procedures For a Liver Transplmentioning
confidence: 76%
“…The incidence of initial treatment failure was lower with balloon dilatation alone (5%) than with balloon dilatation with plastic stent (8%). However, this meta-analysis also found that the rate of stricture recurrence was higher when initial treatment was with balloon dilatation alone versus balloon dilatation and stent placement (33% versus 27%) [51].…”
Section: Variant 3: Initial Therapeutic Procedures For a Liver Transplmentioning
confidence: 76%
“…Today endoscopic therapies are the first‐line treatment option for biliary complications after liver transplantation; however, randomized trials comparing radiologic or surgical therapy vs endo‐therapy are not yet available in this area. This point is firmly confirmed by our national survey.…”
Section: Discussionmentioning
confidence: 99%
“…Benign biliary strictures are mostly related to liver transplantation or chronic pancreatitis [2]. In fact, anastomotic strictures are one of the most common adverse events after liver transplantation, occurring in up to 34% of cases, being more common in transplants with living liver donors [3]. In the recent years, endoscopic treatment with balloon dilation or biliary stent has become the gold standard, and surgical intervention is reserved for unsuccessful or inaccessible strictures to endoscopic treatment [3].…”
mentioning
confidence: 99%
“…In fact, anastomotic strictures are one of the most common adverse events after liver transplantation, occurring in up to 34% of cases, being more common in transplants with living liver donors [3]. In the recent years, endoscopic treatment with balloon dilation or biliary stent has become the gold standard, and surgical intervention is reserved for unsuccessful or inaccessible strictures to endoscopic treatment [3]. Even though the optimal endoscopic strategy for the treatment of these strictures remains to be defined, in a recent metaanalysis, Aparício et al [3] concluded that the endoscopic treatment of anastomotic strictures with fully covered self-expandable metal stents was equally effective as the treatment with plastic stents, but the former was associated with a lower complication risk.…”
mentioning
confidence: 99%
See 1 more Smart Citation